2015
DOI: 10.4085/1062-6050-49.3.93
|View full text |Cite
|
Sign up to set email alerts
|

Injury and Illness Epidemiology at a Summer Sport-Camp Program, 2008 Through 2011

Abstract: Context: University-sponsored summer sport camps often employ athletic trainers; however, there is a dearth of epidemiologic studies describing the injury and illness experience of sport-camp participants to guide clinicians.Objective: To describe the injury and illness experience of youth participants at a university-sponsored summer sport-camp program during a 4-year period.Design: Descriptive epidemiology study. Setting: A National Collegiate Athletic Association Division I university that sponsored 76 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In the injury section, tendon injuries predominate with 72.03%, where the highest percentage is located in LL, mainly in Patellar T.. This is consistent with the epidemiological studies carried out by Barber Foss et al 29 and Oller et al 30 .…”
Section: Discussionsupporting
confidence: 89%
“…In the injury section, tendon injuries predominate with 72.03%, where the highest percentage is located in LL, mainly in Patellar T.. This is consistent with the epidemiological studies carried out by Barber Foss et al 29 and Oller et al 30 .…”
Section: Discussionsupporting
confidence: 89%
“…4 Furthermore, for outcomes assessment to have practical value in a health care discipline and improve patient care, the outcomes measured must reflect the aspects of health that are meaningful to the patient. [5][6][7] Specific to the athletic patient population, authors of epidemiology studies [8][9][10] reported that lower extremity (LE) musculoskeletal injuries accounted for the majority of injuries sustained by this population. An LE injury affects the hip, groin, thigh, knee, shank, ankle, foot, or toes.…”
mentioning
confidence: 99%
“…An LE injury affects the hip, groin, thigh, knee, shank, ankle, foot, or toes. 10 According to the World Health Organization (WHO), musculoskeletal conditions ''encompass a spectrum of conditions, from those of acute onset and short duration to lifelong disorders.'' 11 Musculoskeletal injury has the potential to affect many facets of life, including physical and emotional wellbeing.…”
mentioning
confidence: 99%